Blockade of IL-36 Receptor Signaling Does Not Prevent from TNF-Induced Arthritis - Derer, Anja; Groetsch, Bettina; Harre, Ulrike; Böhm, Christina; Towne, Jennifer; Schett, Georg; Frey, Silke; Hueber, Axel (PLoS ONE, 2014)
Interleukin (IL)-36? is a newly described member of the IL-1 cytokine family with a known inflammatory and pathogenic function in psoriasis. Recently, we could demonstrate that the receptor (IL-36R), its ligand IL-36? and its antagonist IL-36Ra are expressed in synovial tissue of arthritis patients. Furthermore, IL-36? induces MAP-kinase and NF?B signaling in human synovial fibroblasts with subsequent expression and secretion of pro-inflammatory cytokines.To understand the pathomechanism of IL-36 dependent inflammation, we investigated the biological impact of IL-36? signaling in the hTNFtg mouse. Also the impact on osteoclastogenesis by IL-36? was tested in murine and human osteoclast assays.Diseased mice showed an increased expression of IL-36R and IL-36? in inflamed knee joints compared to wildtype controls. However, preventively treating mice with an IL-36R blocking antibody led to no changes in clinical onset and pattern of disease. Furthermore, blockade of IL-36 signaling did not change histological signs of TNF-induced arthritis. Additionally, no alteration on bone homeostasis was observed in ex vivo murine and human osteoclast differentiation assays.Thus we conclude that IL-36? does not affect the development of inflammatory arthriti
EVALuna2:12991

Cancer Cell Death-Inducing Radiotherapy: Impact on Local Tumour Control, Tumour Cell Proliferation and Induction of Systemic Anti-tumour Immunity - Frey, Benjamin; Derer, Anja; Scheithauer, Heike; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo (Advances in Experimental Medicine and Biology, 2016)
Radiotherapy (RT) predominantly is aimed to induce DNA damage in tumour cells that results in reduction of their clonogenicity and finally in tumour cell death. Adaptation of RT with higher single doses has become necessary and led to a more detailed view on what kind of tumour cell death is induced and which immunological consequences result from it. RT is capable of rendering tumour cells immunogenic by modifying the tumour cell phenotype and the microenvironment. Danger signals are released as well as the senescence-associated secretory phenotype. This results in maturation of dendritic cells and priming of cytotoxic T cells as well as in activation of natural killer cells. However, RT on the other hand can also result in immune suppressive events including apoptosis induction and foster tumour cell proliferation. That's why RT is nowadays increasingly combined with selected immunotherapies.
EVALuna2:18359

Chemoradiation Increases PD-L1 Expression in Certain Melanoma and Glioblastoma Cells - Derer, Anja; Spiljar, Martina; Baeumler, Monika; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (Frontiers in Immunology, 2016)
Immunotherapy approaches currently make their way into the clinics to improve the outcome of standard radiochemotherapy (RCT). The programed cell death receptor ligand 1 (PD-L1) is one possible target that, upon blockade, allows T cell-dependent antitumor immune responses to be executed. To date, it is unclear which RCT protocol and which fractionation scheme leads to increased PD-L1 expression and thereby renders blockade of this immune suppressive pathway reasonable. We therefore investigated the impact of radiotherapy (RT), chemotherapy (CT), and RCT on PD-L1 surface expression on tumor cells of tumor entities with differing somatic mutation prevalence. Murine melanoma (B16-F10), glioblastoma (GL261-luc2), and colorectal (CT26) tumor cells were treated with dacarbazine, temozolomide, and a combination of irinotecan, oxaliplatin, and fluorouracil, respectively. Additionally, they were irradiated with a single dose [10 Gray (Gy)] or hypo-fractionated (2 × 5 Gy), respectively, norm-fractionated (5 × 2 Gy) radiation protocols were used. PD-L1 surface and intracellular interferon (IFN)-gamma expression was measured by flow cytometry, and IL-6 release was determined by ELISA. Furthermore, tumor cell death was monitored by AnnexinV-FITC/7-AAD staining. For firstin vivoanalyses, the B16-F10 mouse melanoma model was chosen. In B16-F10 and GL261-luc2 cells, particularly norm-fractionated and hypo-fractionated radiation led to a significant increase of surface PD-L1, which could not be observed in CT26 cells. Furthermore, PD-L1 expression is more pronounced on vital tumor cells and goes along with increased levels of IFN-gamma in the tumor cells. In melanoma cells CT was the main trigger for IL-6 release, while in glioblastoma cells it was norm-fractionated RT.In vivo, fractionated RT only in combination with dacarbazine induced PD-L1 expression on melanoma cells. Our results suggest a tumor cell-mediated upregulation of PD-L1 expression following in particular chemoradiation that is not only dependent on the somatic mutation prevalence of the tumor entity.
EVALuna2:32917
Keywords: fractionated radiotherapy; immunotherapy; checkpoint inhibitor; PD-L1; IFN-gamma; IL-6; melanoma; glioblastoma

Deletion of the receptor tyrosine kinase Tyro3 inhibits synovial hyperplasia and bone damage in arthritis - Ruiz-Heiland, Gisela; Zhao, Yi; Derer, Anja; Braun, Timm; Engelke, Klaus; Neumann, Elena; Mueller-Ladner, Ulf; Liu, Yi; Zwerina, Jochen; Schett, Georg (Annals of the Rheumatic Diseases, 2014)
To test whether the tyrosine kinase Tyro3 affects arthritis. Tyro3, the ligand of growth arrest-specific protein 6 (GAS6) is a receptor tyrosine kinase involved in cell survival. Tyro3 and GAS6 are expressed in the arthritic synovium, and in vitro studies have shown their role in osteoclast differentiation.Bone was assessed by micro CT and histomorphometry in Tyro3-deficient (Tyro3(-/-)) and wild-type mice. Arthritis was induced in both genotypes, and Gas6 level was measured by ELISA. Synovitis, synovial hyperplasia, bone erosion, osteoclast activation and osteoclast gene expression were assessed by histomorphometry and reverse transcriptase-PCR, respectively. In vitro osteoclast differentiation assays were performed in Tyro3(-/-) and wild-type mice. Furthermore, effects of Tyro3 and GAS6 on human synovial fibroblast proliferation and osteoclastogenesis were assessed in human cells.Tyro3(-/-) mice had significantly higher bone mass than wild-type littermates. Induction of arthritis increased GAS6 serum levels. Arthritic Tyro3(-/-) mice showed less synovial hyperplasia, osteoclast numbers and bone damage compared with controls. In vivo expression of osteoclast-associated receptor and receptor activator of nuclear factor-?B and in vitro osteoclastogenesis were impaired in Tyro3(-/-) mice. GAS6 also induced synovial fibroblast proliferation and osteoclast differentiation in human cells in Tyro3-dependent manner.These findings indicate that Tyro3 is a critical signal for synovial hyperplasia, osteoclast differentiation and bone erosion during arthritis. GAS6 and Tyro3 therefore constitute therapeutic targets to inhibit synovial hyperplasia and associated bone erosion.
EVALuna2:10050

Electrothermic effects of microwave heating on B16 melanoma cells - examinations with a semi-continuous plug flow-like reactor - Drescher, C.; Derer, Anja; Rosin, A.; Gerdes, T.; Willert-Porada, M.; Wadepohl, M.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32880

Fractionated radiotherapy is the main stimulus for the induction of cell death and of Hsp70 release of p53 mutated glioblastoma cell lines - Rubner, Yvonne; Muth, Carolin; Strnad, Annedore; Derer, Anja; Sieber, Renate; Buslei, Rolf; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Radiation Oncology, 2014)
Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults. Despite a multimodal therapy consisting of resection followed by fractionated radiotherapy (RT) combined with the chemotherapeutic agent (CT) temozolomide (TMZ), its recurrence is almost inevitable. Since the immune system is capable of eliminating small tumor masses, a therapy should also aim to stimulate anti-tumor immune responses by induction of immunogenic cell death forms. The histone deacetylase inhibitor valproic acid (VPA) might foster this.Reflecting therapy standards, we applied in our in vitro model fractionated RT with a single dose of 2Gy and clinically relevant concentrations of CT. Not only the impact of RT and/or CT with TMZ and/or VPA on the clonogenic potential and cell cycle of the glioblastoma cell lines T98G, U251MG, and U87MG was analyzed, but also the resulting cell death forms and release of danger signals such as heat-shock protein70 (Hsp70) and high-mobility group protein B1 (HMGB1).The clonogenic assays revealed that T98G and U251MG, having mutated tumor suppressor protein p53, are more resistant to RT and CT than U87MG with wild type (WT) p53. In all glioblastoma cells lines, fractionated RT induced a G2 cell cycle arrest, but only in the case of U87MG, TMZ and/or VPA alone resulted in this cell cycle block. Further, fractionated RT significantly increased the number of apoptotic and necrotic tumor cells in all three cell lines. However, only in U87MG, the treatment with TMZ and/or VPA alone, or in combination with fractionated RT, induced significantly more cell death compared to untreated or irradiated controls. While necrotic glioblastoma cells were present after VPA, TMZ especially led to significantly increased amounts of U87MG cells in the radiosensitive G2 cell cycle phase. While CT did not impact on the release of Hsp70, fractionated RT resulted in significantly increased extracellular concentrations of Hsp70 in p53 mutated and WT glioblastoma cells.Our results indicate that fractionated RT is the main stimulus for induction of glioblastoma cell death forms with immunogenic potential. The generated tumor cell microenvironment might be beneficial to include immune therapies for GBM in the future.
EVALuna2:7235

Galectin-3 as a novel regulator of osteoblast-osteoclast interaction and bone homeostasis - Simon, Dominic; Derer, Anja; Andes, Fabian T.; Lezuo, Patrick; Bozec, Aline; Schett, Georg; Herrmann, Martin; Harre, Ulrike (Bone, 2017)
Bone tissue undergoes permanent and lifelong remodeling with a concerted action of bone-building osteoblasts and bone-resorbing osteoclasts. A precise cooperation between those two cell types is critical in the complex process of bone renewal. Galectin-3 is a member of the ?-galactoside-binding lectin family playing multiple roles in cell growth, differentiation and aggregation. As it has been described to be expressed in bone, galectin-3 might influence bone homeostasis by regulating the function and/or interplay of osteoblasts and osteoclasts. Here, we investigated the role of galectin-3 in osteoclastogenesis and osteoblast-osteoclast interactions. Bone histomorphometric analysis and ?CT measurements revealed a decreased trabecular bone volume and an increased osteoclast number in 12weeks old male galectin-3 knockout mice compared to wildtype littermates. Galectin-3 deficient bone marrow cells displayed a higher osteoclastogenic capacity in ex vivo differentiation assays, associated with elevated TRAF6 mRNA levels, suggesting an intrinsic inhibition of osteoclastogenesis by galectin-3 interfering with RANKL-mediated signaling. Furthermore, the addition of extracellular galectin-3 to murine or human osteoclastogenesis assays inhibited osteoclast formation and osteoclast numbers were higher in co-culture assays with galectin-3 deficient osteoblasts. In conclusion, our data suggest the secretion of galectin-3 as a novel mechanism for osteoblasts to control osteoclastogenesis and to maintain trabecular bone homeostasis independently of the RANKL/OPG-axis.
EVALuna2:13345

Hyperthermia with 44 degrees C enhances danger signal-mediated activation of dendritic cells, while immune cell infiltration into tumors is particularly fostered by hyperthermia with lower temperatures - Vogl, P.; Frey, Benjamin; Rueckert, M.; Maueröder, Christian; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (2017)
EVALuna2:32897

Hypofractionated Irradiation Has Immune Stimulatory Potential and Induces a Timely Restricted Infiltration of Immune Cells in Colon Cancer Tumors - Frey, Benjamin; Rueckert, Michael; Weber, Julia; Mayr, Xaver; Derer, Anja; Lotter, Michael; Bert, Christoph; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo (Frontiers in Immunology, 2017)
In addition to locally controlling the tumor, hypofractionated radiotherapy (RT) particularly aims to activate immune cells in the RT-modified microenvironment. Therefore, we examined whether hypofractionated RT can activate dendritic cells (DCs), induce immune cell infiltration in tumors, and how the chronology of immune cell migration into tumors occurs to gain knowledge for future definition of radiation breaks and inclusion of immunotherapy. Colorectal cancer treatments offer only limited survival benefit, and immunobiological principles for additional therapies need to be explored with preclinical models. The impact of hypofractionated RT on CT26 colon cancer tumor cell death, migration of DCs toward supernatants (SN) of tumor cells, and activation of DCs by SN were analyzed. The subcutaneous tumor of a BALB/c-CT26 mouse model was locally irradiated with 2 × 5 Gy, the tumor volume was monitored, and the infiltration of immune cells in the tumor was determined by flow cytometry daily. Hypofractionated RT induced a mixture of apoptotic and necrotic CT26 cells, which is known to be in particular immunogenic. DCs that migrated toward SN of CT26 cells particularly upregulated the activation markers CD80 and CD86 when in contact with SN of irradiated tumor cells. After hypofractionated RT, the tumor outgrowth was significantly retarded and in the irradiated tumors an increased infiltration of macrophages (CD11bhigh/F4-80+) and DCs (MHC-II+), but only between day 5 and 10 after the first irradiation, takes place. While CD4+T cells migrated into non-irradiated and irradiated tumors, CD8+T cells were only found in tumors that had been irradiated and they were highly increased at day 8 after the first irradiation. Myeloid-derived suppressor cells and regulatory T cells show regular turnover in irradiated and non-irradiated tumors. Tumor cell-specific anti-IgM antibodies were enhanced in the serum of animals with irradiated tumors. We conclude that hypofractionated RT suffices to activate DCs and to induce infiltration of innate and adaptive immune cells into solid colorectal tumors. However, the presence of immune cells in the tumor which are beneficial for antitumor immune responses is timely restricted. These findings should be considered when innovative multimodal tumor treatment protocols of distinct RT with immune therapies are designed and clinically implemented.
EVALuna2:32906

Hypofractionated Radiotherapy Upregulates Several Immune Checkpoint Molecules in Head and Neck Squamous Cell Carcinoma Cells Independently of the HPV Status While ICOS-L Is Upregulated Only on HPV-Positive Cells - Wimmer, Sebastian; Deloch, Lisa; Hader, Michael; Derer, Anja; Grottker, Fridolin; Weissmann, Thomas; Hecht, Markus; Gostian, Antoniu-Oreste; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2021)
While the treatment of squamous cell carcinoma of the head and neck (HNSCC) with radiotherapy (RT) is complemented more and more by immunotherapy in clinical trials, little is known about the impact of the human papillomavirus (HPV) status or the applied RT scheme on the immune phenotype of the tumor cells. Therefore, we aimed to examine the impact of the HPV status of four human HNSCC cell lines on cell death and the expression of immune checkpoint molecules (ICMs) after RT with either hypofractionation irradiation (5x3.0Gy) or a high single dose (1x19.3Gy) via multicolor flow cytometry and quantitative PCR at an early time point after therapy. In our study, 5x3.0Gy RT induced high numbers of early and late apoptotic cells independent of the HPV status, but necrosis was only increased in the HPV-positive UM-Scc-47 cells. Generally, the immune stimulatory ICMs (CD70, CD137-L, ICOS-L) were less affected by RT compared to the immune suppressive ones (PD-L1, PD-L2, and the herpesvirus entry mediator (HVEM)). A significant higher surface expression of the analyzed ICMs was found after hypofractionated RT compared to a single high dose; however, regardless of the HPV status, with the exception of ICOS-L. Here, HPV-positive HNSCC tumor cells showed a stronger response to 5x3.0Gy than HPV-negative ones. On the RNA level, only minor alterations of ICMs were observed following RT, with the exception of the HPV negative cell line CAL33 treated with 5x3.0Gy, where PD-L2, HVEM and CD70 were significantly increased. We conclude that the HPV status may not distinctly predict immunological responses following RT, and thus cannot be used as a single predictive marker for therapy responses in HNSCC. In contrast, the patient-specific individual expression of ICMs following RT is preferable for the targeted patient selection for immune therapy directed against distinct ICM.
CRIS-Team WoS Importer:2021-09-17

Immune-modulating properties of ionizing radiation: rationale for the treatment of cancer by combination radiotherapy and immune checkpoint inhibitors - Derer, Anja; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Cancer Immunology Immunotherapy, 2016)
Radiotherapy (RT) utilizes the DNA-damaging properties of ionizing radiation to control tumor growth and ultimately kill tumor cells. By modifying the tumor cell phenotype and the tumor microenvironment, it may also modulate the immune system. However, out-of-field reactions of RT mostly assume further immune activation. Here, the sequence of the applications of RT and immunotherapy is crucial, just as the dose and fractionation may be. Lower single doses may impact on tumor vascularization and immune cell infiltration in particular, while higher doses may impact on intratumoral induction and production of type I interferons. The induction of immunogenic cancer cell death seems in turn to be a common mechanism for most RT schemes. Dendritic cells (DCs) are activated by the released danger signals and by taking up tumor peptides derived from irradiated cells. DCs subsequently activate T cells, a process that has to be tightly controlled to ensure tolerance. Inhibitory pathways known as immune checkpoints exist for this purpose and are exploited by tumors to inhibit immune responses. Cytotoxic T lymphocyte antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1) on T cells are two major checkpoints. The biological concepts behind the findings that RT in combination with anti-CTLA-4 and/or anti-PD-L1 blockade stimulates CD8+ T cell-mediated anti-tumor immunity are reviewed in detail. On this basis, we suggest clinically significant combinations and sequences of RT and immune checkpoint inhibition. We conclude that RT and immune therapies complement one another.
EVALuna2:18336

Immune suppressive properties of Glioblastoma cells might result in part from radiation-induced increased expression of inhibitory immune checkpoint molecules - Langenfelder, E.; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36504

Immunomodulation by ionizing radiation-impact for design of radio-immunotherapies and for treatment of inflammatory diseases - Frey, Benjamin; Rueckert, Michael; Rühle, Paul-Friedrich; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Immunological Reviews, 2017)
Ionizing radiation is often regarded as an element of danger. But, danger responses on the cellular and molecular level are often beneficial with regard to the induction of anti-tumor immunity and for amelioration of inflammation. We outline how in dependence of radiation dose and fraction, radiation itself-and especially in combination with immune modulators-impacts on the innate and adaptive immune system. Focus is set on radiation-induced changes of the tumor cell phenotype and the cellular microenvironment including immunogenic cancer cell death. Mechanisms how anti-tumor immune responses are triggered by radiotherapy in combination with hyperthermia, inhibition of apoptosis, the adjuvant AnnexinA5, or vaccination with high hydrostatic pressure-killed autologous tumor cells are discussed. Building on this, feasible multimodal radio-immunotherapy concepts are reviewed including overcoming immune suppression by immune checkpoint inhibitors and by targeting TGF-β. Since radiation-induced tissue damage, inflammation, and anti-tumor immune responses are interconnected, the impact of lower doses of radiation on amelioration of inflammation is outlined. Closely meshed immune monitoring concepts based on the liquid biopsy blood are suggested for prognosis and prediction of cancer and non-cancer inflammatory diseases. Finally, challenges and visions for the design of cancer radio-immunotherapies and for treatment of benign inflammatory diseases are given.
EVALuna2:32867

Impact of radio(chemo)therapy on expression of immune checkpoint ligands PD-L1 and PD-L2 on murine and human melanoma cells - Riegel, Dania; Bäumler, Monika; Spiljar, Martina; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Derer, Anja; Gaipl, Udo (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32890

Impact of radiotherapy and chemotherapy on PD-L1 and EGF-R expression in melanoma and glioblastoma cells - Bäumler, Monika; Spiljar, Martina; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (DEGRO - Deutsche Gesellschaft dür Radioonkologie e.V., 2016)

Influence and mechanistic principles of radio(chemo) therapy on PD-L1 and EGF-R expression on melanoma and glioblastoma cells - Baeumler, M.; Spiljar, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32877

Influence of fractional Radio(chemo)therapy on the Expression Patterns of immunocheckpoint Molecules on Glioblastoma Cell Lines - Ladinig, A.; Schatz, Johannes; Fischer, R.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Derer, Anja (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Inhibition of bone remodeling in young mice by bisphosphonate displaces the plasma cell niche into the spleen - Teufel, Stefan; Groetsch, Bettina; Luther, Julia; Derer, Anja; Schinke, Thorsten; Amling, Michael; Schett, Georg; Mielenz, Dirk; David, Jean-Pierre (Journal of Immunology, 2014)
The bone marrow provides niches for early B cell differentiation and long-lived plasma cells. Therefore, it has been hypothesized that perturbing bone homeostasis might impact B cell function and Ab production. This hypothesis is highly relevant for patients receiving long-term treatment with antiresorptive drugs. We therefore analyzed the humoral immune response of mice chronically treated with ibandronate, a commonly used bisphosphonate. We confirmed the increased bone mass caused by inhibition of osteoclast activity and also the strongly reduced bone formation because of decreased osteoblast numbers in response to ibandronate. Thus, bisphosphonate drastically inhibited bone remodeling. When ibandronate was injected into mice after a primary immunization to mimic common antiosteoporotic treatments, the generation of the various B cell populations, the response to booster immunization, and the generation of plasma cells were surprisingly normal. Mice also responded normally to immunization when ibandronate was applied to naive mice. However, there, ibandronate shunted the homing of bone marrow plasma cells. Interestingly, ibandronate reduced the numbers of megakaryocytes, a known component of the bone marrow plasma cell niche. In line with normal Ab responses, increased plasma cell populations associated with increased megakaryocyte numbers were then observed in the spleens of the ibandronate-treated mice. Thus, although inhibition of bone remodeling disturbed the bone marrow plasma cell niche, a compensatory niche may have been created by relocating the megakaryocytes into the spleen, thereby allowing normal B cell responses. Therefore, megakaryocytes may act as a key regulator of plasma cell niche plasticity.
EVALuna2:12971

Inosine Released from Dying or Dead Cells Stimulates Cell Proliferation via Adenosine Receptors - Chen, Jin; Chaurio, Ricardo A.; Maueröder, Christian; Derer, Anja; Rauh, Manfred; Kost, Andriy; Liu, Yi; Mo, Xianming; Hueber, Axel; Bilyy, Rostyslav; Herrmann, Martin; Zhao, Yi; et al. (Frontiers in Immunology, 2017)
Many antitumor therapies induce apoptotic cell death in order to cause tumor regression. Paradoxically, apoptotic cells are also known to promote wound healing, cell proliferation, and tumor cell repopulation in multicellular organisms. We aimed to characterize the nature of the regenerative signals concentrated in the micromilieu of dead and dying cells.Cultures of viable melanoma B16F10 cells, mouse fibroblasts, and primary human fibroblast-like synoviocytes (FLS) in the presence of dead and dying cells, their supernatants (SNs), or purified agonists and antagonists were used to evaluate the stimulation of proliferation. Viable cell quantification was performed by either flow cytometry of harvested cells or by crystal violet staining of adherent cells. High-performance liquid chromatography and liquid chromatography coupled with mass spectrometry of cell SNs were deployed to identify the nature of growth-promoting factors. Coimplantation of living cells in the presence of SNs collected from dead and dying cells and specific agonists was used to evaluate tumor growth in vivo.The stimulation of proliferation of few surviving cells by bystander dead cells was confirmed for melanoma cells, mouse fibroblasts, and primary FLS. We found that small soluble molecules present in the protein-free fraction of SNs of dead and dying cells were responsible for the promotion of proliferation. The nucleoside inosine released by dead and dying cells acting via adenosine receptors was identified as putative inducer of proliferation of surviving tumor cells after irradiation and heat treatment.Inosine released by dead and dying cells mediates tumor cell proliferation via purinergic receptors. Therapeutic strategies surmounting this pathway may help to reduce the rate of recurrence after radio- and chemotherapy.
EVALuna2:13419

Interleukin-36 receptor mediates the crosstalk between plasma cells and synovial fibroblasts - Schmitt, Verena; Hahn, Madelaine; Kästele, Verena; Wagner, Olga; Wiendl, Maximilian; Derer, Anja; Taddeo, Adriano; Hahne, Stefanie; Radbruch, Andreas; Jäck, Hans-Martin; Schuh, Wolfgang; Mielenz, Dirk; et al. (European Journal of Immunology, 2017)
The IL-1 family member IL-36? has proinflammatory and pathogenic properties in psoriasis. IL-36? binds to the IL-36 receptor leading to nuclear factor kappa B/mitogen activated protein kinase mediated cytokine release. The IL-36R antagonist prevents recruitment of IL-1 receptor accessory protein and therefore IL-36-dependent cell activation. In inflamed human tissue, we previously could show that resident B cells and plasma cells (PC) express IL-36?. Further, fibroblast-like synoviocytes (FLS) produced proinflammatory cytokines upon IL-36?-stimulation. We hypothesize an IL-36-specific crosstalk between B cells/PCs and FLS permitting a proinflammatory B cell niche. Here, we firstly demonstrated that B cell lines and B cells from healthy donors express IL-36? and stimulation increased IL-36? in B cells and primary plasmablasts/PCs. Moreover, FLS respond specifically to IL-36? by proliferation and production of matrix metalloproteinases via p38/HSP27 signaling. Importantly, IL-36R-deficiency abrogated IL-36?-induced production of inflammatory mediators in FLS and changed the intrinsic FLS-phenotype. Using an in vitro co-culture system, we could show that IL-36R-deficient FLS had a limited capacity to support PC survival compared to wild-type FLS. Hence, we demonstrated an IL-36R-dependent crosstalk between B cells/PCs and FLS. Our data support the concept of initiation and maintenance of a proinflammatory niche by B cells in the joints. This article is protected by copyright. All rights reserved.
EVALuna2:13406

Low dose radiation alters the inflammatory phenotype of fibroblast-like synoviocytes and impacts on bone metabolism - Frey, Benjamin; Liberg, J.; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32862

Low-Dose Radiotherapy Ameliorates Advanced Arthritis in hTNF-α tg Mice by Particularly Positively Impacting on Bone Metabolism - Deloch, Lisa; Derer, Anja; Hueber, Axel; Herrmann, Martin; Schett, Georg; Wölfelschneider, Jens; Hahn, Jonas; Rühle, Paul-Friedrich; Stillkrieg, Willy; Fuchs, Jana; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2018)
Inflammation and bone erosion are central in rheumatoid arthritis (RA). Even though effective medications for control and treatment of RA are available, remission is only seen in a subset of patients. Treatment with low-dose radiotherapy (LD-RT) which has been already successfully used for amelioration of symptoms in benign diseases should be a promising approach to reduce pain, inflammation, and particularly bone erosion in patients with RA. Even though anti-inflammatory effects of LD-RT are already described with non-linear dose response relationships, and pain-reducing effects have been clinically observed, the underlying mechanisms are widely unknown. Besides immune cells many other cell types, such as fibroblast-like synoviocytes (FLS), osteoclasts, and osteoblast are present in the affected joint and might be modulated by LD-RT. For this study, these cell types were obtained from human tumor necrosis factor-α transgenic (hTNF-α tg) mice and were consecutively exposed to different doses of ionizing radiation (0.1, 0.5, 1.0, and 2.0 Gy, respectively) in vitro. In order to study the in vivo effects of LD-RT within the arthritic joint, hind paws of arthritic hTNF-α tg mice were locally irradiated with 0.5 Gy, a single dose per fraction that is known for good clinical responses. Starting at a dose of 0.5 Gy, proliferation of FLS was reduced and apoptosis significantly enhanced with no changes in necrosis. Further, expression of RANK-L was slightly reduced following irradiation with particularly 0.5 Gy. Starting from 0.5 Gy, the numbers of differentiated osteoclasts were significantly reduced, and a lower bone resorbing activity of treated osteoclasts was also observed, as monitored via pit formation and Cross Laps presence. LD-RT had further a positive effect on osteoblast-induced mineralization in a discontinuous dose response relationship with 0.5 Gy being most efficient. An increase of the gene expression ratio of OPG/RANK-L at 0.1 and 0.5 Gy and of production of OPG at 0.5 and 1.0 Gy was observed. In vivo, LD-RT resulted in less severe arthritis in arthritic hTNF-α tg mice and in significant reduction of inflammatory and erosive area with reduced osteoclasts and neutrophils. Locally applied LD-RT can, therefore, induce a beneficial micro-environment within arthritic joints by predominantly positively impacting on bone metabolism.
EVALuna2:34663
Keywords: rheumatoid arthritis; inflammation; low-dose radiotherapy; bone metabolism; synovial-like fibroblasts; osteoclasts; osteoblasts

Mitoxantrone-loaded nanoparticles for magnetically controlled tumor therapy–induction of tumor cell death, release of danger signals and activation of immune cells - Ratschker, Teresa; Egenberger, Laura; Alev, Magdalena; Zschiesche, Lisa; Band, Julia; Schreiber, Eveline; Frey, Benjamin; Derer, Anja; Alexiou, Christoph; Janko, Christina (Pharmaceutics, 2020)
Stimulating the patient`s immune system represents a promising therapeutic strategy to fight cancer. However, low immunogenicity of the tumor cells within an immune suppressive milieu often leads to weak anti-tumor immune responses. Additionally, the immune system may be impaired by accompanying aggressive chemotherapies. We show that mitoxantrone, bound to superparamagnetic iron oxide nanoparticles (SPIONs) as the transport system, can be magnetically accumulated in adherent HT-29 colon carcinoma cells, thereby inducing the same cell death phenotype as its soluble counterpart, a chemotherapeutic agent and prototypic inductor of immunogenic cell death. The nanoparticle-loaded drug induces cell cycle stop, apoptosis and secondary necrosis in a dose-and time-dependent manner comparable to the free drug. Cell death was accompanied by the release of interleukin-8 and damage-associated molecular patterns (DAMPs) such as HSP70 and ATP, which fostered chemotactic migration of monocytes and maturation of dendritic cells. We furthermore ensured absence of endotoxin contaminations and compatibility with erythrocytes and platelets and investigated the influence on plasma coagulation in vitro. Summarizing, with magnetic enrichment, mitoxantrone can be accumulated at the desired place, sparing healthy peripheral cells and tissues, such as immune cells. Conserving immune competence in cancer patients in the future might allow combined therapeutic approaches with immune therapies (e.g. checkpoint inhibitors).
CRIS-Team Scopus Importer:2020-10-09
Keywords: Cell death; Chemotherapy; Iron oxide nanoparticles; Magnetic drug targeting; Nanomedicine

Modern Radiotherapy Concepts and the Impact of Radiation on Immune Activation - Derer, Anja; Hartmann, Josefin; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Frontiers in Oncology, 2016)
Even though there is extensive research carried out in radiation oncology, most of the clinical studies focus on the effects of radiation on the local tumor tissue and deal with normal tissue side effects. The influence of dose fractionation and timing particularly with regard to immune activation is not satisfactorily investigated so far. This review, therefore, summarizes current knowledge on concepts of modern radiotherapy (RT) and evaluates the potential of RT for immune activation. Focus is set on radiation-induced forms of tumor cell death and consecutively the immunogenicity of the tumor cells. The so-called non-targeted, abscopal effects can contribute to anti-tumor responses in a specific and systemic manner and possess the ability to target relapsing tumor cells as well as metastases. The impact of distinct RT concepts on immune activation is outlined and pre-clinical evidence and clinical observations on RT-induced immunity will be discussed. Knowledge on the radiosensitivity of immune cells as well as clinical evidence for enhanced immunity after RT will be considered. While stereotactic ablative body radiotherapy seem to have a beneficial outcome over classical RT fractionation in pre-clinical animal models, in vitro model systems suggest an advantage for classical fractionated RT for immune activation. Furthermore, the optimal approach may differ based on the tumor site and/or genetic signature. These facts highlight that clinical trials are urgently needed to identify whether high-dose RT is superior to induce anti-tumor immune responses compared to classical fractionated RT and in particular how the outcome is when RT is combined with immunotherapy in selected tumor entities.
EVALuna2:18361

Moonlighting osteoclasts as undertakers of apoptotic cells - Harre, Ulrike; Keppeler, Hildegard; Ipseiz, Natacha; Derer, Anja; Poller, Kerstin; Aigner, Michael; Schett, Georg; Herrmann, Martin; Lauber, Kirsten (Autoimmunity, 2012)
Created from Fastlane, Scopus look-up
Keywords: Apoptotic cell clearance; Dying cell clearance; Efferocytosis; Osteoclasts; Phagocytosis; Rheumatoid arthritis

Normofractionated irradiation and not temozolomide modulates the immunogenic and oncogenic phenotype of human glioblastoma cell lines - Schatz, Julia; Ladinig, Alexandra; Fietkau, Rainer; Putz, Florian; Gaipl, Udo; Frey, Benjamin; Derer, Anja (Strahlentherapie und Onkologie, 2022)
Purpose Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor, with an overall poor prognosis after diagnosis. Conventional treatment includes resection, chemotherapy with temozolomide (TMZ), and concomitant radiotherapy (RT). The recent success of immunotherapy approaches in other tumor entities, particularly with immune checkpoint inhibitors, could not be clinically transferred to GBM treatment so far. Therefore, preclinical analyses of the expression of both immune-suppressive and immune-stimulatory checkpoint molecules following treatment of human glioblastoma cells with RT and/or temozolomide is needed to design feasible radio(chemo)immunotherapy trials for GBM in the future. Methods Five human glioblastoma cell lines (H4, HROG-06, U118, U138, U251) were analyzed regarding their clonogenic survival and cell death forms after chemotherapy (CT) with TMZ and/or normofractionated RT (5 x 2 Gy) via multicolor flow cytometry. Further, the tumor cell surface expression of immune-activating (OX40L, CD137L, CD70, and ICOSL) and immune-suppressive (PD-L1, PD-L2, HVEM) checkpoint molecules and of an oncogenic molecule (EGFR) were measured via multicolor flow cytometry after CT and RT alone or after RCT. Results Normofractionated RT and not TMZ was the trigger of induction of predominantly necrosis in the glioblastoma cells. Notably, clonogenicity did not correlate with cell death induction by RT. The basal expression level of immune-suppressive PD-L1, PD-L2, and HVEM varied in the analyzed glioblastoma cells. RT, but not TMZ, resulted in a significant upregulation of PD-L1 and PD-L2 in all tumor cells investigated. Also, the expression of HVEM was increased after RT in most of the GBM cell lines. In contrast, normofractionated RT individually modulated expression of the stimulating immune checkpoint molecules CD70, CD137L, OX40L, and ICOSL1. The oncogenic factor EGFR was significantly increased by irradiation in all examined cell lines, albeit to a different extent. None of the investigated molecules were downregulated after the treatments. Conclusion Normofractionated radiotherapy modulates the immunogenic as well as the oncogenic phenotype of glioblastoma cells, partly individually. Therefore, not only PD-L1 and PD-L2, but also other immunogenic molecules expressed on the surface of glioblastoma cells could serve as targets for immune checkpoint blockade in combination with RT in the future.
CRIS-Team WoS Importer:2022-12-23

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317

Radio(chemo)therapy does differently impact on PD-L1 and PD-L2 expression in human melanoma cell lines - Derer, Anja; Riegel, D.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36496

Radio-Immunotherapy-Induced Immunogenic Cancer Cells as Basis for Induction of Systemic Anti-Tumor Immune Responses - Pre-Clinical Evidence and Ongoing Clinical Applications - Derer, Anja; Deloch, Lisa; Rubner, Yvonne; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (Frontiers in Immunology, 2015)
Radiotherapy (RT) primarily aims to locally destroy the tumor via the induction of DNA damage in the tumor cells. However, the so-called abscopal, namely systemic and immune-mediated, effects of RT move over more and more in the focus of scientists and clinicians since combinations of local irradiation with immune therapy have been demonstrated to induce anti-tumor immunity. We here summarize changes of the phenotype and microenvironment of tumor cells after exposure to irradiation, chemotherapeutic agents, and immune modulating agents rendering the tumor more immunogenic. The impact of therapy-modified tumor cells and damage-associated molecular patterns on local and systemic control of the primary tumor, recurrent tumors, and metastases will be outlined. Finally, clinical studies affirming the bench-side findings of interactions and synergies of radiation therapy and immunotherapy will be discussed. Focus is set on combination of radio(chemo)therapy (RCT) with immune checkpoint inhibitors, growth factor inhibitors, and chimeric antigen receptor T-cell therapy. Well-deliberated combination of RCT with selected immune therapies and growth factor inhibitors bear the great potential to further improve anti-cancer therapie
EVALuna2:18276

Rsk2 controls synovial fibroblast hyperplasia and the course of arthritis - Derer, Anja; Boehm, Christina; Groetsch, Bettina; Gruen, Joachim R.; Gruetzkau, Andreas; Stock, Michael; Böhm, Sybille; Sehnert, Bettina; Gaipl, Udo; Schett, Georg; Hueber, Axel; David, Jean-Pierre (Annals of the Rheumatic Diseases, 2016)
Arthritis is a chronic inflammatory disease characterised by immune cell infiltration and mesenchymal cell expansion in the joints. Although the role of immune cells in arthritis is well characterised, the development of mesenchymal cell hyperplasia needs to be better defined. Here, we analysed the role of the ribosomal S6 kinase Rsk2, which we found to be highly activated in joints of patients with arthritis, in the development of mesenchymal cell hyperplasia.We genetically inactivated Rsk2 in the tumour necrosis factor (TNF)-? transgenic (TNFtg) mice, an animal model for human inflammatory arthritis. Clinical and histological signs of arthritis as well as molecular markers of inflammation and joint destruction were quantified. Fibroblast-like synoviocytes (FLS) were characterised in vitro and the effect of Rsk2 deletion on the pattern of gene expression was determined.Rsk2 deficiency in TNFtg mice results in earlier and exacerbated inflammation as well as increased bone and cartilage destruction. The production of inflammatory cytokines, matrix metalloproteinases and osteoclastogenic molecules was significantly increased in vivo upon Rsk2 inactivation. Bone marrow deficient in Rsk2 could not transfer this phenotype, indicating that Rsk2 expression in mesenchymal cells controls the course of arthritis. Indeed, Rsk2 deficiency was associated with a more activated phenotype and higher proliferative capacity of FLS, thereby increasing cytokines and production of matrix proteinases.Rsk2 emerges as a key regulator of mesenchymal cell numbers in the joint and thereby could be targeted to control the inflammatory and tissue-destructive feature of joints in arthritis.
EVALuna2:13016

T cells as key players for bone destruction in gouty arthritis? - Harre, Ulrike; Derer, Anja; Schorn, Christine; Schett, Georg; Herrmann, Martin (Arthritis Research & Therapy, 2011)
The deposition of monosodium urate (MSU) crystals in synovial fluid and tissue leads to gouty arthritis frequently associated with synovial inflammation and bone erosions. The cellular mechanism that links MSU crystals to an increased number of osteoclasts has not yet been fully understood. In a recent issue of Arthritis Research & Therapy Lee and colleagues proposed that bone destruction in chronic gouty arthritis is at least in part dependent on expression by T cells of receptor activator of NF-κB ligand (RANKL). The authors showed that pro-resorptive cytokines such as IL-1β, IL-6, and TNFα are expressed within tophi and stromal infiltrates. In vitro stimulation with MSU crystals revealed monocytes as a source for these cytokines, whereas T cells produce RANKL, the major trigger of osteoclastogenesis. © 2011 BioMed Central Ltd.
Created from Fastlane, Scopus look-up

The AP-1 transcription factor Fra1 inhibits follicular B cell differentiation into plasma cells - Groetsch, Bettina; Brachs, Sebastian; Lang, Christiane; Luther, Julia; Derer, Anja; Schlötzer-Schrehardt, Ursula; Bozec, Aline; Fillatreau, Simon; Berberich, Ingolf; Hobeika, Elias; Reth, Michael; Wagner, Erwin F.; et al. (Journal of Experimental Medicine, 2014)
The cornerstone of humoral immunity is the differentiation of B cells into antibody-secreting plasma cells. This process is tightly controlled by a regulatory gene network centered on the transcriptional repressor B lymphocyte-induced maturation protein 1 (Blimp1). Proliferation of activated B cells is required to foster Blimp1 expression but needs to be terminated to avoid overshooting immune reactions. Activator protein 1 (AP-1) transcription factors become quickly up-regulated upon B cell activation. We demonstrate that Fra1, a Fos member of AP-1, enhances activation-induced cell death upon induction in activated B cells. Moreover, mice with B cell-specific deletion of Fra1 show enhanced plasma cell differentiation and exacerbated antibody responses. In contrast, transgenic overexpression of Fra1 blocks plasma cell differentiation and immunoglobulin production, which cannot be rescued by Bcl2. On the molecular level, Fra1 represses Blimp1 expression and interferes with binding of the activating AP-1 member c-Fos to the Blimp1 promoter. Conversely, overexpression of c-Fos in Fra1 transgenic B cells releases Blimp1 repression. As Fra1 lacks transcriptional transactivation domains, we propose that Fra1 inhibits Blimp1 expression and negatively controls plasma cell differentiation through binding to the Blimp1 promoter. In summary, we demonstrate that Fra1 negatively controls plasma cell differentiation by repressing Blimp1 expression.
EVALuna2:13013

THE IMPACT OF LOW-DOSE RADIATION ON INFLAMMATORY DISEASES - Deloch, Lisa; Derer, Anja; Hueber, Axel; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2016)
EVALuna2:32924